Williwaw! - Bodett, Tom. (New York : A. Knopf, 2000)
In their father's absence, thirteen-year-old September and her younger brother Ivan disobey his orders by taking the boat out on their Alaska bay, where they are caught in a terrifying storm called a Williwaw.
"A Knopf paperback."
5.9
5-8
Keywords: Storms -- Alaska -- Fiction; Boats and boating -- Alaska -- Fiction; Brothers and sisters -- Alaska -- Fiction; Alaska -- Fiction